Alloantibody Responses After Renal Transplant Failure Can Be Better Predicted by Donor–Recipient HLA Amino Acid Sequence and Physicochemical Disparities Than Conventional HLA Matching. Issue 7 (1st March 2016) - Kosmoliaptsis, V.; Mallon, D. H.; Chen, Y.; Bolton, E. M.; Bradley, J. A.; Taylor, C. J.
Abstract : We have assessed whether HLA immunogenicity as defined by differences in donor–recipient HLA amino‐acid sequence (amino‐acid mismatch score, AMS; and eplet mismatch score, EpMS) and physicochemical properties (electrostatic mismatch score, EMS) enables prediction of allosensitization to HLA, and also prediction of the risk of an individual donor–recipient HLA mismatch to induce donor‐specific antibody (DSA). HLA antibody screening was undertaken using single‐antigen beads in 131 kidney transplant recipients returning to the transplant waiting list following first graft failure. The effect of AMS, EpMS, and EMS on the development of allosensitization (calculated reaction frequency [cRF]) and DSA was determined. Multivariate analyses, adjusting for time on the waiting list, maintenance on immunosuppression after transplant failure, and graft nephrectomy, showed that AMS (odds ratio [OR]: 1.44 per 10 units, 95% CI: 1.02–2.10, p = 0.04) and EMS (OR: 1.27 per 10 units, 95% CI: 1.02–1.62, p = 0.04) were independently associated with the risk of developing sensitization to HLA (cRF > 15%). AMS, EpMS, and EMS were independently associated with the development of HLA‐DR and HLA‐DQ DSA, but only EMS correlated with the risk of HLA‐A and ‐B DSA development. Differences in donor–recipient HLA amino‐acid sequence and physicochemical properties enable better assessment of the risk of HLA‐specific sensitization than conventional HLA matching. Abstract : This study applies the Cambridge HLA Immunogenicity Algorithm to assess alloantibody responses after a failed kidney transplant and provides strong evidence that amino acid sequence and physicochemical analyses of donor–recipient HLA immunogenicity enables prediction of HLA class I and II donor‐specific alloantibody development and offers additional value to that of conventional HLA mismatch grade for predicting overall HLA‐specific sensitization to the potential donor pool.